Penyusunan Materi Pembelajaran Penggunaan Aplikasi Siplah Pada UMKM - Fendy Cuandra; Anjela Anjela (ConCEPt - Conference on Community Engagement Project, 2021)
SIPlah is a digital marketplace for the procurement of goods and services in educational units is a strategic step to take advantage of the potential of the digital marketplace which is used by more than 63 thousand schools out of 440 thousand schools throughout Indonesia. The socialization of SIPLah is a necessary thing to do, especially for MSMEs that the education market ecosystem can support the growth and benefit of MSMEs in Indonesia. This study aims to conduct material preparation and training for MSMEs using the SIPlah platform as a digital marketplace to help the growth and development of MSMEs. Learning material is divided into two forms, namely material in the form of video and digital modules. This material is implemented through training and demonstrations to employees of Toko Modern Sukses in person and online. After training and material implementation, store employees can operate the application independently. Also, Toko Modern Sukses has a new marketplace and a significant increase in Toko Modern Sukses revenue by 50.63%.